Perancangan Antarmuka Aplikasi Penggajian Karyawan CV. Kuranji Karya Mandiri Menggunakan Metode Human Centered Design (HCD) - Weni Gusti Rahayu; Ismiarta Aknuranda; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Kuranji Karya Mandiri is one of the premier furniture manufacturers and commerce in Indonesia. CV. Kuranji Karya Mandiri has never implemented a computer-based information system in doing employee and payroll records. This has the potential to lead to misinformation because of employees who cheat in attendance and employment information. CV. An independent work requires an information system that can help companies manage data. Based on these problems, the research designed a user interface of the payroll application in a human centered design method (HCD). HCD is a method that involves humans as users in every stage of the design process. The stages of this study include defining context by observation, interviews and literacy studies, defining user requirements through business and use case models, producing design solutions through navigation design and prototypes that suit usability guidelines, evaluating the design with brainwashing focus groups to ensure user's suitability to interface and to improve design solutions. The results of the FGD evaluation are standard for improving design solutions in accordance with that which has been agreed with FGD participants. Improving the prototype became the result of this study with the goal of demonstrating a solution for delivery of the payday information with a level of leverage appropriate to the context of use.